2003
DOI: 10.1073/pnas.1434429100
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell diversity revealed by global expression profiling

Abstract: The vascular system is locally specialized to accommodate widely varying blood flow and pressure and the distinct needs of individual tissues. The endothelial cells (ECs) that line the lumens of blood and lymphatic vessels play an integral role in the regional specialization of vascular structure and physiology. However, our understanding of EC diversity is limited. To explore EC specialization on a global scale, we used DNA microarrays to determine the expression profile of 53 cultured ECs. We found that ECs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
549
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 678 publications
(589 citation statements)
references
References 36 publications
34
549
1
5
Order By: Relevance
“…In spite of HUVEC are often used to study endothelial mechanisms, experiments were developed in HUAEC in an attempt to determine if those genetic differences could alter the response to estradiol and to atherogenic compounds like oxLDL. Despite their common developmental origins, endothelial cells are not identical, differing widely in morphology and function, and existing different genes expressed specifically by the endothelium of arteries (Chi et al, 2003). Fetal circulation is rather different from adult as gas exchange does not occur in the lungs but in the placenta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of HUVEC are often used to study endothelial mechanisms, experiments were developed in HUAEC in an attempt to determine if those genetic differences could alter the response to estradiol and to atherogenic compounds like oxLDL. Despite their common developmental origins, endothelial cells are not identical, differing widely in morphology and function, and existing different genes expressed specifically by the endothelium of arteries (Chi et al, 2003). Fetal circulation is rather different from adult as gas exchange does not occur in the lungs but in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of umbilical arteries carry deoxygenated blood at relatively low blood pressure, some evidences have shown that the specification of arterial and venous identity is largely genetically determined (dela Paz and D'Amore, 2009). In fact, phylogenetic approaches show the identity of umbilical arteries to different arteries in the body and the same occurs with veins (Chi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high degree of heterogeneity has been observed for endothelial cells isolated from different tissues and/or animal species. Also, significant differences exist between large-vessel and microvascular endothelium [13][14][15]. Nevertheless, the bulk of experimental evidence indicate that different members of the FGF family, mostly FGF1 and FGF2, can induce in vitro a complex ''proangiogenic phenotype'' in endothelial cells ( Fig.…”
Section: In Vitro Effects On Endothelial Cellsmentioning
confidence: 99%
“…ZD6126 has significant antitumour effects in a wide range of histologically distinct subcutaneous tumour xenografts in nude mice . However, the efficacy of ZD6126 has not been examined at orthotopic sites where the endothelia are phenotypically distinct and tumour growth is likely to be more physiologically relevant to human disease (Craig et al, 1998;Chi et al, 2003).…”
mentioning
confidence: 99%